Application of digital PCR and next generation sequencing in the etiology investigation of a foodborne disease outbreak caused by Vibrio parahaemolyticus. (December 2019) - Li, Ying; Zhang, Shuang; Li, Jie; Chen, Meiling; He, Mu; Wang, Yuanyuan; Zhang, Yanchun; Jing, Hongbo; Ma, Hongmei; Li, Yindong; Zhao, Lin; Zhao, Hongqun; et al.
Abstract: Globally, V. parahaemolyticus infection is a leading cause of bacterial diarrheal diseases. Pathogenic V. parahaemolyticus strains that produce hemolysins are responsible for these diseases. The composition of pathogenic and non-pathogenic V. parahaemolyticus and the change of the bacterial composition before and after traditional selective enrichment in a single sample associated with disease outbreak remain unclear. We investigated an outbreak by using next generation sequencing and digital PCR to address those questions. NGS showed that the V. parahaemolyticus caused the outbreak belonged to s single clone. In contrast, among the seven non-pathogenic V. parahaemolyticus isolated from the suspected food sample, 4 serotypes and 6 PFGE patterns were identified. And nearly 70, 000 SNPs were identified among the non-pathogenic strains. This result confirmed that the outbreak was caused by V. parahaemolyticus . Furthermore, NGS results clearly showed the diversity of non-pathogenic V. parahaemolyticus in a single contaminated food sample. The ratios of non-pathogenic and pathogenic V. parahaemolyticus were 31.41 and 620.11 in the original and enriched food samples respectively showed by digital PCR. Meta-genomic data indicated the top 3 species were Weissella cibaria, Weissella confusa, and Enterobacter cloacae in the original food sample, and Vibrio sp Ex25, Vibrio sp 712i, and V. parahaemolyticus in the enriched sample. Therefore, the combing of NGS and digital PCR results showed that traditional Vibrio selective enrichment media could facilitate the growth of Vibrios, however, it provided no advantages to pathogenic V. parahaemolyticus . Hence, our results indicated that the traditional culture methods alone may lead to wrong conclusions and so improvements in culture methods are needed. Highlights: Pathogenic V. parahaemolyticus that caused disease outbreak were highly clonal. High genomic diversity in V. parahaemolyticus isolated from a single food sample. Pathogenic V. parahaemolyticus ratio decreased after traditional sample enrichment.